Promoting Generative AI Literacy among Students and Teachers - Mohamed Soltani, Hafed Zarzour & Ammar Ladjailia (Springer Nature Switzerland, 2025)
Recent advancements in artificial intelligence (AI) techniques, particularly generative AI models like ChatGPT and Gemini, have demonstrated significant progress across various domains, by transforming the way we live, learn, and teach. The integration of generative AI (Gen AI) in education opens a new perspective by providing tools able to generate educational resources (courses, exercises, simulations, summaries) personalized and interactive; Gen AI has the potential to make more satisfying and effective learning. However, their integration raises significant challenges, and ethics is mandatory. Although some studies have investigated the use of such models in education, their understanding and integration within educational settings, both for students and teachers, remain unexplored. This chapter explores the importance of promoting Gen AI literacy among students and teachers. It will discuss the benefits and potential challenges of integrating Gen AI into the learning activities and provide strategies for fostering responsible and effective use of this technology.